HISTORICAL DISCIPLINES IN MODERN HIGHER EDUCATION INSTITUTIONS AND THEIR ROLE IN THE FORMATION OF STUDENT’S PERSONALITY - Nailya F. Tagirova; Elena I. Sumburova (Высшее образование в России)
The article suggests developed on the basis of the federal state education standards cross-cutting themes and problem-chronological modules to ensure continuity in studying the economic university disciplines as «History» and «Economic history». The authors dwell upon the interdisciplinary links and interactive forms of training taking into account the competence-based approach and psychological and age-related peculiarities of modern students.